Usability Study of an Augmented Reality Game for Philippine History - Rodrigo, Ma. Mercedes T. (Archīum Ateneo, 2016)
We investigate the extent to which Augmented Reality can contribute to effectiveness and enjoyment in the context of history-game-based learning. This paper presents a series of usability tests of a mobile Augmented Reality game application for learning Philippine history, Igpaw: Intramuros, with representatives of the game’s target audience. These tests discovered issues that compromised player enjoyment, including fatigue during gameplay, hurdles in learning AR-specific game mechanics, game repetitiveness, and outdoor safety concerns, in addition to minor technical issues. Nevertheless, the tests show the game’s high effectivity in teaching Philippine history.